Results from Australia's 2014 Report Card on Physical Activity for Children and Youth - Schranz, Natasha; Olds, Tim; Cliff, Dylan; Davern, Melanie; Engelen, Lina; Giles-Corti, Billie; Gomersall, Sjaan; Hardy, Louise; Hesketh, Kylie; Hills, Andrew; Lubans, David; Macdonald, Doune; et al. (My University, 2014)
Background: Like many other countries, Australia is facing an inactivity epidemic. The purpose of the Australian 2014 Physical Activity Report Card initiative was to assess the behaviors, settings, and sources of influences and strategies and investments associated with the physical activity levels of Australian children and youth. Methods: A Research Working Group (RWG) drawn from experts around Australia collaborated to determine key indicators, assess available datasets, and the metrics which should be used to inform grades for each indicator and factors to consider when weighting the data. The RWG then met to evaluate the synthesized data to assign a grade to each indicator. Results: Overall Physical Activity Levels were assigned a grade of D-. Other physical activity behaviors were also graded as less than average (D to D-), while Organized Sport and Physical Activity Participation was assigned a grade of B-. The nation performed better for settings and sources of influence and Government Strategies and Investments (A- to a C). Four incompletes were assigned due to a lack of representative quality data. Conclusions: Evidence suggests that physical activity levels of Australian children remain very low, despite moderately supportive social, environmental and regulatory environments. There are clear gaps in the research which need to be filled and consistent data collection methods need to be put into place.
Journal of Physical Activity and Health
Keywords: Adolescents and youth; Childhood and child development; Health and wellbeing